2016
DOI: 10.1016/j.jaci.2015.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal geohelminth infections on allergy in early childhood

Abstract: BackgroundMaternal geohelminth infections during pregnancy may protect against allergy development in childhood.ObjectiveWe sought to investigate the effect of maternal geohelminths on the development of eczema, wheeze, and atopy during the first 3 years of life.MethodsA cohort of 2404 neonates was followed to 3 years of age in a rural district in coastal Ecuador. Data on wheeze and eczema were collected by means of questionnaire and physical examination at 13, 24, and 36 months of age. Atopy was measured base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 28 publications
4
38
0
1
Order By: Relevance
“…The cross-sectional [2] and case–control studies [17,18] were considered high quality, while the cohort studies [1,1216,19] were considered moderate or high quality.…”
Section: Resultsmentioning
confidence: 99%
“…The cross-sectional [2] and case–control studies [17,18] were considered high quality, while the cohort studies [1,1216,19] were considered moderate or high quality.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have also evaluated the cross-reactivity between rBlo t 5 and the group 21 allergens, as well as with crude extracts of B. tropicalis and Ascaris lumbricoides [12,53]. The latter allergen source should be considered in tropical regions due to the high prevalence of helminth infections [54,55,56], which could possibly interfere with the serodiagnosis of mite allergy [57,58]. Interestingly, Carvalho et al [12] showed that rBlo t 5 and rBlo t 21 are less cross-reactive with A. lumbricoides crude extracts than with extracts of B. tropicalis , suggesting that these 2 recombinant allergens might represent markers for the diagnosis of B. tropicalis- sensitized patients.…”
Section: Allergens Of B Tropicalismentioning
confidence: 99%
“…Epidemiological studies examining the relationships between helminth infections, which are highly prevalent in low-income countries, and allergic disorders have provided evidence for an inverse association between helminth infections and allergic disorders [3, 7, 8]. The strongest evidence for the association between helminth infections and allergy has been provided by small intervention studies that have shown increases in the prevalence or the risk of atopy after anthelmintic treatment of infected children [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…As in the case of allergic disorders, chronic helminth infections induce a strong T-helper 2 (Th2) immune response that leads to elevated levels of immunoglobulin E (IgE), eosinophils, basophils, and mast cells [8, 14]. However, unlike immune responses induced by allergens, helminth infections also lead to increased anti-inflammatory cytokines, such as interleukin (IL-10) and transforming growth factor-β [5, 16].…”
Section: Introductionmentioning
confidence: 99%